Ownership Form and Consumer Welfare: Evidence from the Nursing Home Industry - Rexford E. Santerre; John A. Vernon (SAGE Publishing, 2007)
This paper compares the likely consumer benefits of higher quality with the potentially greater production costs that result from increased not-for-profit activity in a nursing home services market area. The comparison of consumer benefits and costs is made possible by observing empirically how an increased market penetration of not-for-profit facilities affects the use of private-pay nursing home care. Increased (decreased) use of nursing home care suggests that the consumer benefits associated with additional not-for-profit nursing homes are greater (less) than consumer costs. The empirical results indicate that, from a consumer's perspective, too few not-for-profit nursing homes may exist in the typical market area of the United States. The policy implication is that more quality of care per dollar might be obtained by attracting a greater percentage of not-for-profit nursing homes into many market areas.